Ensuring Occupational Safety and Health in Medical Record Storage at the Medical Records Installation - Nindia Putri; Asiqah Lidia (Inovasi Analisis Data, 2024)
Background: Handling medical records risks staff safety; an investigation found inadequate PPE use, dusty conditions, and risks from sharp edges.Methods: This descriptive qualitative study aimed to evaluate workplace health and safety in medical record storage. Data were collected through observations and interviews and then analyzed descriptively to understand the current safety measures and their effectiveness.Result Innovation: The findings indicate that although safety measures are in place, they are not fully effective. Notably, there are no specific standard operating procedures (SOPs) for occupational safety in handling medical records. The use of PPE, such as gloves and masks, is insufficient, with gloves being used only 41% of the time.Novelty: This study highlights the gaps in current safety practices and the critical need for specific SOPs for occupational safety in medical record management. It underscores the importance of enhancing the utilization of PPE to ensure the safety of staff members.Implications and Theory: The study suggests that improving safety standards and increasing the use of personal protective equipment (PPE) can significantly enhance the protection of staff involved in medical record handling. This has broader implications for workplace health and safety, emphasizing the need for comprehensive safety protocols and effective implementation of PPE in similar settings